The Ethics of Natural Law according to Thomas Aquinas - Stančienė, Dalia Marija (Verbum – Analecta Neolatina, 2004)
Thomas Aquinas' concept of law is an example of the application of Aristotelian teleology to the integral theory of ethics, law and governing. Aquinas' concept of natural law is called moral law by many scholars. Man is able to anticipate the law of action in relation to eternal law, and such participation in eternal law Thomas calls natural law. The ethics starts from the principle good is to be done and evil is to be avoided. This principle is the basis for the rest of the ethical precepts concerning what is to be done and what is to be avoided. Man has innate general orientations on how to live and behave in this world. Conscience evaluates and judges the motives and moral qualities of actions. This is the main idea of natural law, which is described in the article.